2021
DOI: 10.1101/2021.07.09.451847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations in Drosophila tRNA processing factors cause phenotypes similar to Pontocerebellar Hypoplasia

Abstract: Mature tRNAs are generated by multiple RNA processing events, which can include the excision of intervening sequences. The tRNA splicing endonuclease (TSEN) complex is responsible for cleaving these intron-containing pre-tRNA transcripts. In humans, TSEN copurifies with CLP1, an RNA kinase. Despite extensive work on CLP1, its in vivo connection to tRNA splicing remains unclear. Interestingly, mutations in CLP1 or TSEN genes cause neurological diseases in humans that are collectively termed Pontocerebellar Hypo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Previous studies on human samples and animal models indicated that hypoplasia results from degeneration and cell death, respectively (Barth et al, 2007; Kasher et al, 2011; Schmidt et al, 2022). We therefore investigated whether elevated levels of apoptosis could explain the reduced size of PCH2a cerebellar and neocortical organoids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on human samples and animal models indicated that hypoplasia results from degeneration and cell death, respectively (Barth et al, 2007; Kasher et al, 2011; Schmidt et al, 2022). We therefore investigated whether elevated levels of apoptosis could explain the reduced size of PCH2a cerebellar and neocortical organoids.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in different systems, tRNAs can directly regulate apoptosis (Avcilar-Kucukgoze and Kashina, 2020; Mei et al, 2010). Neurodegeneration and apoptosis have been suggested to occur in the cerebellum of affected individuals with PCH based on neuropathological observations (Barth et al, 2007) and in animal models of PCH (Ishimura et al, 2014; Kasher et al, 2011; Schmidt et al, 2022), respectively. However, our analysis of cCas3-positive cells did not reveal any differences in apoptosis between PCH2a and control cerebellar and neocortical organoids at D30 and D50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A rare disease caused by a shared mechanism or a family of unrelated, yet similar diseases PCH is a rare autosomal recessive disease primarily caused by mutations in RNA processing factors. In addition to the many fly model organisms mentioned above, several new fly PCH models have recently been developed (Morton et al, 2020;Schmidt et al, 2021;Slavotinek et al, 2020), which may be useful tools to better characterize and understand PCH. PCH appears to primarily be caused by dysfunction in RNA processing machinery, with a couple of exceptions.…”
Section: Pchmentioning
confidence: 99%
“…Mammalian TSEN additionally associates with the RNA kinase CLP1 by uncharacterized interactions 1,30 . While in vitro experiments showed that CLP1 is dispensable for pre-tRNA splicing 10,19 , in vivo and in-cell studies connected mutations in CLP1 to impaired pre-tRNA splicing and neurodegeneration 7,8,[31][32][33] . Indeed, mutations in CLP1 and all four subunits of human TSEN have been associated with pontocerebellar hypoplasia (PCH), a broad group of inherited neurodegenerative disorders [2][3][4][5][6][7][8]31,34 .…”
Section: Mainmentioning
confidence: 99%